Korean food made simple - Joo, Judy (Houghton Mifflin Harcourt, 2016)
"125 simple Korean recipes from the host of the Cooking Channel television show of the same name In Korean Food Made Simple, Judy Joo, host of the Cooking Channel's show of the same name and Food Network regular, brings Korean food to the masses, proving that it's fun and easy to prepare at home. As a Korean-American, Judy understands how to make dishes that may seem exotic and difficult accessible to the everyday cook. The book has over 100 recipes including well-loved dishes like kimchi, sweet potato noodles (japchae), beef and vegetable rice bowl (bibimbap), and Korean fried chicken, along with creative, less-traditional recipes like Spicy Pork Belly Cheese Steak, Krazy Korean Burgers, and Fried Fish with Kimchi Mayo and Sesame Mushy Peas. In addition, there are chapters devoted to sauces, desserts, and drinks as well as a detailed list for stocking a Korean pantry, making this book a comprehensive guide on Korean food and flavors. Enjoying the spotlight as the hot Asian cuisine, Korean food is on the rise, and Judy's bold and exciting recipes are go-tos for making it at home. "--